Nano-Gold and Film-Globular Nanostructures in Samples of Native Gold Deposit Pioneer (Amur Region, Russia) - P. P. Safronov; N. V. Moiseenko; I. V. Kuznetsova (Georesursy, 2025)
The study of native gold from several ore zones of the Pioneer field (Amur). In the samples found: nano-gold of various morphology, varying size and composition, as well as complex micro- and nanostructures (film, film layered rhythmic, globular, fine disperse, etc.). In clay-micaceous mineral phases associated with native gold, an isometric and spheroidal nanogold visible under an electron microscope with particle sizes ~ 30–600 nm and a composition of both pure gold (sample 1000 %) and silver impurities (sample ~ 980 %). In the matrix of the same mineral phases, an invisible ultra-thin nanogold was detected, which is recorded by energy dispersive X-ray analysis (size < 30–50 nm, its sample is 1000 %). The genesis of the above types of nanogold is associated primarily with imperfections (defects) in the crystalline structure of the minerals that make up the gold-associating rock. These defects were geochemical barriers on which thin and ultra-thin gold was deposited. A xenomorphic nano-gold is also mounted on the surface of a row of golden, with elongated shapes dominating the particles. The particle sizes of this gold range from the first tens of nanometers to 600–700 nm, although there are particles up to 1000 nm in length and sample 803 %. Various film and globular structures, represented by stratified rhythmic nano-formations consisting of alternating gold films, planar and curved films on the gold surface and globular particles, have been identified in a number of samples of native gold (globules) of gold. The thickness of the films generally varies in the range of ~ 50 to 450 nm, and the size of the globule – from 250 to 670 nm, the composition is different. Mean sample of gold films from the Southern Ore Zone 948 % in Intermediate 880 %. The complex structure of the gold with the presence of various micro- and nanostructures indicates the multi-stage processes of formation of native gold in different ore zones of the Pioneer deposit.